Studi Sifat Termal Prekursor In(TMHD)3 untuk Menumbuhkan Lapisan Tipis In2O3 dengan Teknik MOCVD - Horasdia Saragih; Hasniah Aliah; Euis Sustini; Sukirno Sukirno (Institut Teknologi Bandung, 2009)
The In2O3 thin films have been deposited on quartz substrate by MOCVD technique using In(TMHD)3 as a metal organic precurcor. Thermal properties of In(TMHD)3 have been investigated by analyses of TG-DTA curve and FTIR spectrum to determine the value of In2O3 deposition parameters. Based on TG-DTA curve and FTIR spectrum analyses, we find that: (1) melting point of In(TMHD)3 powder is 175 °C; (2) In(TMHD)3 powder starts to evaporate at 184 °C; (3) partial oxidation of In(TMHD)3 in Ar/atmosfer accur at 260 °C; and (4) dissosiation of TMHD ligand from indium metal element happened in the temperature range of 300 °C - 400 °C. Following these results, we maintaned growth condition for deposition of In2O3: the temperature of In(TMHD)3 bubbler (Tb) = 200 °C; the pressure of In(TMHD)3 bubbler (Pb) = 260 Torr; the rate of argon gas flow to carry out the vapor of In(TMHD)3 = 50 sccm; the rate of oxygen gas = 50 sccm; and temperature of substrate = 300 °C. In 120 minutes, the thickness of deposited In2O3 thin films, the rate of deposition and the roughness of film surface are about 0.2 µm, 1.6x10-3 µm/menit and 70 nm, respectively.